(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Purpose Post Office investment schemes play a significant role in promoting financial inclusion in India, particularly among women investors who often prefer safe and accessible investment avenues. The purpose of this study is to examine women investors’ perceptions, attitudes, and responses toward Post Office investment schemes and to assess their role as instruments of financial inclusion through the lens of investment behaviour. Design/methodology/approach The study adopts a quantitative descriptive research design based on secondary data. Unlike traditional survey-based studies, this research utilizes "Revealed Preference Theory," inferring investor perception from actual behavioural data. Data was collated from the Ministry of Finance (Lok Sabha/Rajya Sabha Starred Questions), Department of Posts Annual Reports, and RBI statistics covering the period 2019–2025. Findings The analysis reveals a strong behavioural preference for government-backed schemes among women. The rapid uptake of the Mahila Samman Savings Certificate (43.30 lakh accounts in 18 months) and the sustained growth of Sukanya Samriddhi Yojana (4.10 crore accounts) indicate that "Safety" and "Institutional Trust" are the primary drivers of women's financial inclusion. The study confirms that despite the rise of digital banking, the Post Office remains a critical "safe haven" for women's capital. Originality/value This study contributes to the literature by utilizing macro-level government data to validate micro-level assumptions about women's risk aversion. It provides empirical evidence of the "Trust Factor" in public sector financial institutions.